Innovations and Challenges in Applied Linguistics from the Global South - Alastair Pennycook, Sinfree Makoni (2019)
Innovations and Challenges in Applied Linguistics from the Global South provides an original appraisal of the latest innovations and challenges in applied linguistics from the perspective of the Global South. Global South perspectives are encapsulated in struggles for basic, economic, political and social transformation in an inequitable world, and are not confined to the geographical South. Taking a critical perspective on Southern theories, demonstrating why it is important to view the world from Southern perspectives and why such positions must be open to critical investigation, this book: